TREATMENT WITH ELORES™ FOR UROSEPSIS DUE TO MULTI DRUG RESISTANT Pseudomonas aeruginosa - Sharma, Rajan (Innovare Journal of Medical Sciences, 2016)
Introduction: Urosepsis is a type of sepsis caused by infection of urogenital tract and characterized with inflammatory response. Ability of Pseudomonas aeruginosa to develop resistance to various antibiotics presents as a therapeutic challenge for the physician. Case presentation: In the present case report we discuss a case of 70 years old male patient suffering with urosepsis due to multi drug resistant Pseudomonas aeruginosa pathogen. This patient was treated with a novel antibiotic adjuvant Elores™ (ceftriaxone+sulbactam+EDTA). Conclusion: Present case shows Elores™ to be safe and efficacious in treatment of urosepsis due to multi drug resistant (MDR) Pseudomonas aeruginosa. Elores™ can be considered as drug of choice in treatment of MDR Pseudomonas aeruginosa infections.